Genetic Diversity Assessment of Grass Pea (Lathyrus sativus L.) Varieties from Southern Bangladesh Using RAPD Markers (Plant Tissue Culture and Biotechnology, 2026)
Grass pea (Lathyrus sativus L.) is a promising crop for sustainable agriculture due to its low water demand and drought resistance. Its wider cultivation is constrained by low yield and the neurotoxin oxalyl diamino propionic acid (ODAP). To facilitate genetic improvement, this study assessed the genetic diversity of ten grass pea varieties (V1-V10), including five Bangladesh Agricultural Research Institute (BARI) lines and five local lines from southern Bangladesh, using 12 RAPD primers. The RAPD analysis generated a clear genetic fingerprint for the varieties, producing 549 bands (300 bp-5000 bp) with an overall polymorphism rate of 84.35%. UPGMA cluster analysis grouped the varieties into two major clusters, indicating substantial genetic variability. Genetic distances ranged from 0.1371 to 0.6292, with the highest similarity between V7 (Madaripur) and V8 (Barishal) and the greatest divergence between V1 (BARI Khesari-1) and V8 (Barishal). These findings provide molecular insights that can guide breeding programs to enhance agronomic traits, reduce neurotoxin ODAP levels, and develop DNA-based profiling systems for variety registration.Plant Tissue Cult. & Biotech. 35(2): 389-397, 2025 (December)